2021
DOI: 10.31053/1853.0605.v78.n3.32619
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of intraoperative neuromonitoring during percutaneous cement discoplasty

Abstract: Introduction: Percutaneous cement discoplasty is a minimally invasive procedure to treat low back pain due to advanced degenerative disc disease in elderly patients. Complications of this procedure has been described such as infection, vertebral fracture, cement leakage and nerve injury. Intraoperative neuromonitoring is used to detect the latter. The objective of this study was to assess the usefulness of neuromonitoring during discoplasty to detect new neurological compromise. Methods: 100 consecutive patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Neuro-monitoring, installed during anaesthesia induction, allowed to prevent radicular irritation by changing the cannula entry point in their practice without increasing surgical length. A study on the utility of intraoperative neurophysiological monitoring during PCD reported a sensitivity of 82% and specificity of 99% ( 23 ). Before cement injection was introduced, one paper used a medium injected in the disc to assess the volume of required cement ( 17 ).…”
Section: Resultsmentioning
confidence: 99%
“…Neuro-monitoring, installed during anaesthesia induction, allowed to prevent radicular irritation by changing the cannula entry point in their practice without increasing surgical length. A study on the utility of intraoperative neurophysiological monitoring during PCD reported a sensitivity of 82% and specificity of 99% ( 23 ). Before cement injection was introduced, one paper used a medium injected in the disc to assess the volume of required cement ( 17 ).…”
Section: Resultsmentioning
confidence: 99%